Critical aspects of gender in conflict resolution, peacebuilding, and social movements - Snyder, Anna C.; Stobbe, Stephanie P. (Bingley, U.K. : Emerald, 2011)
This volume of Research in Social Movements, Conflicts and Change explores the important dimension of gender and how women are key contributors to conflict resolution, peace, and social movements throughout the world. Womens networks and their collective activism have increased social justice, peace, and reconciliation in communities. Grassroots initiatives from women groups have positively impacted relationships, peace processes, and peace treaties. The volume includes scholarly research that highlights womens activism in countries such as Sierra Leone, Liberia, El Salvador, Czech Republic, Uzbekistan, South Africa, and United States. Critical issues of poverty, violence, civil wars, inequality, sexual identity, and peace are examined from a gendered perspective.
Introduction / Anna Christine Snyder, Stephanie Phetsamay Stobbe -- A gendered analysis of refugee transnational bridgebuilding capacity / Anna C. Snyder -- The Soukhouan ritual : the legacy of Lao women in conflict resolution / Stephanie P. Stobbe -- Collective action as a space of agency, power, and knowledge : a case study of gaps / Zulfiya M. Tursunova -- Partial justice and reconciliation for Sierra Leone women but reparations and reform remain elusive / Lyn S. Graybill -- New social movements, old gender games? : locating girls in the sport for development and peace movement / Megan Chawansky -- Mobilizing minutewomen : gender, cyberpower, and the new nativist movement / Jennifer L. Johnson -- Collective identity and gendered activism in the Czech environmental movement : the south bohemian mothers' struggle against nuclear power / Alison E. Adams, Thomas E. Shriver -- Recruiting or retaining? : frame reception in the women's peace movement / Rachel V. Kutz-Flamenbaum -- 'The phrase of the day' : examining contexts and co-optation of reproductive justice activism in the women's movement / Zakiya T. Luna.
Keywords: Social Science -- Gender Studies; Social Science -- Feminism & Feminist Theory; Political Science -- Political Freedom & Security -- General; Gender studies, gender groups; Women social reformers -- Cross-cultural studies